Factors Affecting Income Distribution in Sulawesi - Andi Riyanto; Syarwani Canon; Ivan Rahmad Santoso (Jambura Equilibrium Journal, 2022)
This study aims to determine the factors that influence the distribution of income in Sulawesi. The data used is data sourced from the Central Statistics Agency, for the period 2011-2020 in 6 Sulawesi Island Provinces. The method used is multiple regression analysis with the help of the eviews 9 application. The results show that per capita expenditure has a positive and significant effect on income distribution, average years of schooling has a negative and significant effect on income distribution, life expectancy has a negative but not significant effect on income distribution.